Misorientation characteristics of rapid moving boundaries during grain growth in Fe-3%Si alloys. Issue 1 (April 2015) - Mao, W; Yang, P
Abstract: Based on a large amount of experimental observations on highly mobile Σ17, Σ19, and Σ9 coincidence site lattice boundaries (CSLB), the average jump distances of atoms in connection with misorientation were calculated during boundary migration, which indicated that Σ9 CSLB demonstrate not only a stable structure, but also higher mobility than other boundaries because of the actual lowest jump distance if the boundaries move. The higher mobility could even keep more or less if the misorientation of boundaries deviates from exact Σ9 in a limited extent. Therefore, Goss grains could grow rapidly in the matrix with many 111<112> grains since the misorientation between Goss and 111<112> is close to Σ9.